Contextualizing Second Language Anxiety in Multilingual Higher Education: Classroom Conditions and Clinical Settings - Busayo O Ige (International Journal of Teaching and Learning in Higher Education, 2026)
In South African universities, multilingual students whose first language is not English face distinct challenges that impact academic participation and success. This qualitative study examines how second language (L2) anxiety shapes first-year students’ classroom and clinical experiences at the University of Cape Town. Drawing on open-ended survey data, the study reveals that fear of negative evaluation, communicative apprehension, and prevailing language ideologies contribute to students’ reluctance to speak, feelings of invisibility, and withdrawal from engagement. Although anxiety tends to lessen over time, it rarely disappears completely. Notably, students experienced anxiety differently across settings: classroom discussions elicited greater fear and self-censorship, while clinical interactions, often involving shared linguistic and cultural backgrounds, felt less intimidating. Findings highlight the need for systemic, structural interventions that validate diverse English varieties and promote inclusive, low-anxiety learning environments through pedagogical and institutional reform.